The Influence of Corporate Governance Perception Index, Profit Management, and Industrial Type To Environmental Disclosure. - Amanda Chrysanti; Diena Noviarini (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
Thisresearchaims to empirically analyze the influence ofCorporate Governance Perception Index, earnings management,and industry type on environmental disclosure. Environmental Disclosure is the dependent variables in this research were measured by scoring technique based on GRI3.1 Guidelines. For the independent variables in this research, using Corporate Governance Perception Index were measured by CGPI index score, earnings management were measured by discretionary accruals, and industry type were measured bycategorial. This research uses secondary data which population are companies entered Corporate Governance Perception Index in 2009-2012. While the sampling method used was purposive sampling method which is overall 44 sample choose. This research uses multiple regression method to test the hypothesis with SPSS computer program. From the analysis performed in this research, it can be concluded that Corporate Governance Perception Index has positively and significant influence to environmental disclosure. The other hand earnings management has no significant influence to environmental disclosure. The last one industry type has negatively and significant influence to environmental disclosure. Key Words: Corporate Governance Perception Index, Earnings Management, Industry Type, and Environmental Disclosure